Study of Thermodynamic Parameters and Viscosity Behavior of Substituted Pyrazolines in 70% Dioxane-Water-Part—II* - Raghuwanshi, P.B.; Narwade, M.L.; Doshi, A.G. (Asian Journal of Chemistry, 2010)
Viscosity measurements have been made on system comprising 1-carboxamido-3-(2'-hydroxy-3'-bromo-5'-chlorophenyl)-5-phenyl Δ2-pyrazoline (ligand 1) and 1-carboxamido-3-(2'-hydroxy-3'-nitro- 5'-chlorophenyl)-5-phenyl-Δ2-pyrazoline (ligand 2) in 70% dioxanewater mixture solvent at different temperatures. The data have been used to calculate viscosity and thermodynamic parameters, such as ΔG*, ΔH* and ΔS*. We have also studied the effect of solvent on the viscosity at 30°C. It has been found that viscosity increases with increase in the percentage of dioxane. Also viscosity increases due to increase in the concentration of ligand 1 and ligand 2 in 70% dioxane-water mixture. In the presnt investigation β-coefficient value of ligand 2 is greater than the value of ligand 1 in dioxane-water mixture. We have also calculated the thermodynamic parameters ΔG*, ΔH* and ΔS* for ligand 1 and ligand 2 which showed that the process is spontaneous and irreversible.